2001
DOI: 10.1093/aje/153.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Socioeconomic Status and All-Cause Mortality

Abstract: This study sought to determine the contribution of neighborhood socioeconomic status to all-cause mortality and to explore its correlates. As part of the longitudinal "Gezondheid en LevensOmstandigheden Bevolking en omstreken" (GLOBE) study in the Netherlands, 8,506 randomly selected men and women aged 15-74 years from 86 neighborhoods in the city of Eindhoven reported on their socioeconomic status in the 1991 baseline survey. During the 6-year follow-up, 487 persons died. Neighborhood socioeconomic status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
160
3
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(174 citation statements)
references
References 44 publications
5
160
3
6
Order By: Relevance
“…17 Reijneveld reported a statistically significantly increased risk of obesity (BMI > 27) in the most vs the least deprived tertile of neighbourhood deprivation for some, but not all, indicators of neighbourhood deprivation, after adjustment for three measures of individual SEP. 8 An increased risk of obesity by increasing levels of neighbourhood deprivation, independent of individual educational level, was found by Sundquist et al 18 In the Renfrew and Paisley study, age and social class adjusted mean BMI increased significantly (P < 0.01) with increasing neighbourhood deprivation in females, but not in males. 3 The latter study suggests that the association between neighbourhood deprivation and overweight may be modified by individual socio-demographic factors, which has been found for other CHD risk factors as well. 9 This may be due to differences in the importance of, and time spend in neighbourhoods between subgroups.…”
Section: Introductionmentioning
confidence: 68%
“…17 Reijneveld reported a statistically significantly increased risk of obesity (BMI > 27) in the most vs the least deprived tertile of neighbourhood deprivation for some, but not all, indicators of neighbourhood deprivation, after adjustment for three measures of individual SEP. 8 An increased risk of obesity by increasing levels of neighbourhood deprivation, independent of individual educational level, was found by Sundquist et al 18 In the Renfrew and Paisley study, age and social class adjusted mean BMI increased significantly (P < 0.01) with increasing neighbourhood deprivation in females, but not in males. 3 The latter study suggests that the association between neighbourhood deprivation and overweight may be modified by individual socio-demographic factors, which has been found for other CHD risk factors as well. 9 This may be due to differences in the importance of, and time spend in neighbourhoods between subgroups.…”
Section: Introductionmentioning
confidence: 68%
“…Table 3 addressed hypothesis 1b that respondents entered public housing after being diagnosed with their health conditions. First, however, Table 3 presents data from a HOPE VI study 10 that was updated with information from our Atlanta public housing sample in order to assess the quality of our data. Comparisons of diagnosed chronic conditions between US Black women from the National Health Interview Survey (NHIS) found in column 1, the HOPE VI panel study found in column 2, and the Atlanta public housing sample in columns 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…7 High-poverty neighborhoods have been associated with cardiovascular disease and all-cause mortality. [8][9][10] Concentrated poverty also has been associated with myriad social and physical ills, from high unemployment rates, high school dropout rates, single female-headed households, crime, to physical and mental health. [11][12][13][14][15] Determining if public housing itself contributes to the social and physical ills found among those living in extreme poverty is beyond the scope of a single paper; therefore, we limit ourselves to addressing a single issue in this paper: that of public housing residents' health.…”
mentioning
confidence: 99%
“…1-3 Social, institutional, and physical characteristics of neighborhoods are being linked to a variety of health behaviors 4-6 and outcomes 7 including substance abuse, 8, 9 asthma, 10 cardiovascular disease, 11, 12 birth outcomes, 13-15 respiratory infections, 16 sexually transmitted diseases, 17 cancer, 18 and all-cause mortality. [19][20][21][22] Methodologic concerns remain, 3, 23-28 however, including specification of social, institutional and physical characteristics of neighborhoods that should be included in such research; appropriate methods for collecting neighborhood data (e.g., resident surveys, secondary source data, and/or direct, Correspondence and reprints requests: Linda Weiss, PhD, Office of Special Populations, The New York Academy of Medicine, 1216 Fifth Avenue, New York, NY 10029, Tel: 212-822-7298; Fax: 212-876-4220; E-mail: lweiss@nyam.org. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: Introductionmentioning
confidence: 99%